The discourse of austerity in the British press - Grundmann, Reiner; Kreischer, Kim-Sue; Scott, Mike (Nomos, 2018)
In this paper we analyse the discourse of austerity in British broadsheets. Theoretically, we combine insights from discourse analysis and political science. Methodologically, we present a novel procedure to build and analyse a robust corpus derived from LexisNexis. Our analysis of this corpus shows the powerful actors in the discourse, and how they were able to exercise this power through ideas and language. Their visibility in the press, and their discursive performance are crucial elements in our analysis. Our analysis of the discourse shows that austerity has negative connotations; that no independent economic expertise was visible; that George Osborne was the most influential actor, providing clever catchphrases; that the oppositional Labour Party failed to develop an alternative narrative; that journalists took up elements of Osborne’s narrative rather than developing their own; and that right-wing think tanks had little visibility.